PENGARUH PENGETAHUAN PERPAJAKAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK - Kurnia, Anastasya Sumargo; Hidayat, Vinny Stephanie (Unversitas Prof. Dr. Moestopo (Beragama), 2025)
The objective of this study is to examine the impact of taxation knowledge and tax sanctions on the compliance behaviour of motor vehicle taxpayers at Samsat Cimahi. Hence, a sample size of 124 individuals was chosen. Questionnaires were distributed to collect the data. Data analysis involved the utilization of multiple regression analysis. The results of the verified tests indicate that taxpayer knowledge regarding tax sanctions and tax knowledge has a significant and positive impact on tax compliance.